Protein Binding on the Surface of Magnetic Nanoparticles. (3rd June 2019) - Sun, Jiaojiao; Shi, Haimei; Mo, Tianlu; Zhang, Yinglu; Wang, Xudong; Ding, Chuanfan; Yu, Shaoning
Abstract: Magnetic nanoparticles (MNPs) are widely used in the areas of biology and biomedicine. The interaction between MNPs and proteins plays a crucial role in the bioapplication of MNPs, and the binding affinity of protein–MNPs is the manifestation of this interaction. The binding affinity of some proteins with MNPs modified in various ways is determined by fluorescence quenching. The results show that the binding affinity depends on the properties of both the MNPs and the proteins. The higher the surface curvature of MNPs, the larger the MNP, and the higher the binding affinity. No significant difference is found in binding affinity between MNPs with different modification methods. For proteins, the binding affinity depends on the properties of individual proteins, such as the amino acid sequence, the native protein conformation in solution, the isoelectric point, and surface potential. In general, the binding affinity is higher for proteins with cysteine residues on the surface. In addition, pH affects the binding affinity between proteins and MNPs; positively charged proteins and lower pH are more suitable for MNP binding due to electrostatic forces. Abstract : The general rule of binding affinity between proteins and magnetic nanoparticles (MNPs) modified in various ways is addressed. The larger the MNP, the higher the binding affinity. In addition, the binding affinity is higher for proteins with more surface cysteine residues. Positively charged proteins and lower pH are found to be more suitable conditions for MNP–protein binding.